Optimizing Solvent Type and Concentration of Cnidoscolus aconitifolius Leaf Extract to Enhance Chlorophyll Content in Zea mays: Unveiling the Potential of Biostimulant Application in Maize Cultivation - Aulya, Nailul Rahmi; Noli, Zozy Aneloi; Suwirmen, Suwirmen; Utami, Annisa Wulan Agus; Shayen, Millania Putri; Marta, Fepi Dwi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Maize (Zea mays L.) is one of the major cereal commodities with a strategic role in various sectors of societal needs. The application of plant-derived biostimulants has emerged as an alternative approach for enhancing plant physiological performance, including the use of leaf extract from Cnidoscolus aconitifolius (chaya). This study aimed to evaluate the effects of different solvent types and extract concentrations of C. aconitifolius leaves on the chlorophyll content of maize plants. A two-factor Completely Randomized Design (CRD) was used, consisting of: (a) solvent types (aqueous, ethanol, methanol, and butanol) and (b) extract concentrations (control, 25 mg/L, 50 mg/L, and 100 mg/L). The results indicated that neither solvent type nor extract concentration had a significant effect on any chlorophyll parameter. However, the aqueous-based extract at 25 mg/L tended to produce the highest chlorophyll a and total chlorophyll content, while the highest chlorophyll b content was observed in the 25 mg/L butanol extract treatment. In contrast, the 100 mg/L ethanol extract treatment showed a tendency toward the lowest chlorophyll content. These findings suggest that the effectiveness of C. aconitifolius extract as a photosynthetic biostimulant in Z. mays remains limited and is likely influenced by the solubility of its bioactive compounds in the solvents used.